2014
DOI: 10.1111/jgh.12656
|View full text |Cite
|
Sign up to set email alerts
|

PNPLA3 gene polymorphism and response to lifestyle modification in patients with nonalcoholic fatty liver disease

Abstract: Although the PNPLA3 rs738409 GG genotype confers a higher risk of NAFLD, these patients are more sensitive to the beneficial effects of lifestyle modification and should be encouraged to do so.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
3
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(105 citation statements)
references
References 25 publications
5
93
3
4
Order By: Relevance
“…KD have also been associated with a higher decrease in liver volume compared with a standard hypocaloric diet, probably due to the depletion of liver glycogen [59]. Finally, the response to KD may be influenced by genetic predisposition to NAFLD, as shown by two studies with a better response to KD for patients with variants of the PNPLA3 gene [60,61]. When fed a KD, subjects with PNPLA3 variants had a lower liver fat content than controls.…”
Section: Resultsmentioning
confidence: 99%
“…KD have also been associated with a higher decrease in liver volume compared with a standard hypocaloric diet, probably due to the depletion of liver glycogen [59]. Finally, the response to KD may be influenced by genetic predisposition to NAFLD, as shown by two studies with a better response to KD for patients with variants of the PNPLA3 gene [60,61]. When fed a KD, subjects with PNPLA3 variants had a lower liver fat content than controls.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, our previous study has shown that lifestyle modifi cation despite modest weight reduction is helpful for the treatment of NAFLD ( 33 ). Furthermore, carriers of the PNPLA3 G allele experience greater improvement in liver fat aft er lifestyle modifi cation ( 34 ). As most non-obese NAFLD patients are carriers of the G allele, these patients would likely benefi t from lifestyle modifi cation.…”
Section: Non-obese Fatty Livermentioning
confidence: 97%
“…Interestingly, children carrying the PNPLA3 prosteatotic allele seemed to benefit the most from the weight loss [16] . A recent analysis of 154 adult patients in whom hepatic fat contents were quantified with proton-magnetic resonance spectroscopy also showed that individuals carrying the PNPLA3 risk allele might benefit the most from lifestyle changes [29] . The recent analysis of the WELCOME trial, a 15-18 month intervention with omega-3 fatty acids in patients with NAFLD demonstrated that carriage of the PNPLA3 p.148MM genotype influenced the change in liver fat and docosahexaenoic acid (DHA) tissue enrichment [23] .…”
Section: Discussionmentioning
confidence: 99%